2012
DOI: 10.1111/j.1365-3040.2012.02560.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of photoperiodic competency causes phenological mismatch in balsam poplar (Populus balsamifera L.)

Abstract: Plant phenology is expected to be sensitive to climate warming. In boreal trees, spring flush is primarily temperature driven, whereas height growth cessation and autumn leaf senescence are predominantly controlled by photoperiod. Cuttings of 525 genotypes from the full range of balsam poplar were planted into two common gardens (Vancouver and Indian Head, Canada) at similar latitudes, but with differing winter temperatures and growing seasons. There was clinal variation in spring and, particularly, summer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 38 publications
2
80
0
1
Order By: Relevance
“…Conversely, if the hybrid embryo matures faster than the maternal tissues, then the reverse cross may not suffer the same fate as the embryo would be fully developed prior to capsule dehiscence, although there may not be sufficient maternally derived endosperm to support the early development of the embryo leading to delayed or abnormal embryos. This hypothesis is complicated by the fact that P. deltoides and P. balsamifera also exhibit latitudinal variation in phenology of flowering (Braatne et al 1996; Soolanayakanahally et al 2013). For instance, Riemenschneider et al (2001) showed that male P. trichocarpa x female P. deltoides crosses with fathers from northern provenances had higher rates of success than those from crosses with fathers from southern provenances.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, if the hybrid embryo matures faster than the maternal tissues, then the reverse cross may not suffer the same fate as the embryo would be fully developed prior to capsule dehiscence, although there may not be sufficient maternally derived endosperm to support the early development of the embryo leading to delayed or abnormal embryos. This hypothesis is complicated by the fact that P. deltoides and P. balsamifera also exhibit latitudinal variation in phenology of flowering (Braatne et al 1996; Soolanayakanahally et al 2013). For instance, Riemenschneider et al (2001) showed that male P. trichocarpa x female P. deltoides crosses with fathers from northern provenances had higher rates of success than those from crosses with fathers from southern provenances.…”
Section: Discussionmentioning
confidence: 99%
“…The material sequenced consisted of genomic DNA from xylem tissue collected from multiple genotypes in replicate from two environmentally divergent common gardens34. The common gardens are located at Prince Albert (PA - 53.62°N 106.43°W; elevation 461 m) and Indian Head (IH - 50.52°N 103.68°W; elevation 605 m), Saskatchewan, Canada and comprise provenances of P. balsamifera that were collected throughout the natural range of this species.…”
Section: Methodsmentioning
confidence: 99%
“…This phenotypic variation itself diverged among the different climate clusters. Our study dissected the influence of climate (specifically, temperature and precipitation), yet much of the variation in phenology is also attributed to photoperiod ( [71,72,45]). The tight photoperiodic control of traits such as bud set, height growth cessation, and leaf senescence ( [73,74,59]) is crucial both for resistance to cold temperatures and maximization of the growing season, particularly in trees originating from high-latitude and/or high elevation provenances ( [75,56]).…”
Section: Resultsmentioning
confidence: 99%